The Effect Of Entrepreneur Competency And External Factors On The Performance Of Small-Medium Industry In South Sulawesi - Sultan Sultan; Yusran Paris; Sapriyadi Sapriyadi; Lukman S; Aditya Halim Perdana Kusuma Putra (International Journal of Artificial Intelligence Research, 2022)
This study examines the influence of entrepreneurial competence and external factors on the performance of small and medium industries in South Sulawesi Province. The results showed that the influence of Entrepreneurial Competence on the performance of small and medium industries was positive and significant, which means that an increase in the Entrepreneurial Competence factor would significantly impact the improvement of small and medium industries. The influence of external factors on the performance of small and medium industries is positive and significant, which means that an increase in external factors will significantly impact the improvement of small and medium industries